Esco2 regulates cx43 expression during skeletal regeneration in the zebrafish fin. Issue 1 (25th November 2015) - Banerji, Rajeswari; Eble, Diane M.; Iovine, M. Kathryn; Skibbens, Robert V.
Abstract : Background: Roberts syndrome (RBS) is a rare genetic disorder characterized by craniofacial abnormalities, limb malformation, and often severe mental retardation. RBS arises from mutations in ESCO2 that encodes an acetyltransferase and modifies the cohesin subunit SMC3. Mutations in SCC2/NIPBL (encodes a cohesin loader), SMC3 or other cohesin genes ( SMC1, RAD21/MCD1 ) give rise to a related developmental malady termed Cornelia de Lange syndrome (CdLS). RBS and CdLS exhibit overlapping phenotypes, but RBS is thought to arise through mitotic failure and limited progenitor cell proliferation while CdLS arises through transcriptional dysregulation. Here, we use the zebrafish regenerating fin model to test the mechanism through which RBS‐type phenotypes arise.Results : esco2 is up‐regulated during fin regeneration and specifically within the blastema. esco2 knockdown adversely affects both tissue and bone growth in regenerating fins—consistent with a role in skeletal morphogenesis. esco2 ‐knockdown significantly diminishes cx43/gja1 expression which encodes the gap junction connexin subunit required for cell–cell communication. cx43 mutations cause the short fin ( sof b123 ) phenotype in zebrafish and oculodentodigital dysplasia (ODDD) in humans. Importantly, miR‐133‐dependent cx43 overexpression rescues esco2 ‐dependent growth defects.Conclusions : These results conceptually link ODDD to cohesinopathies and provide evidence that ESCO2 may play a transcriptional role critical for human development. Developmental Dynamics 245:7–21, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: esco2 is expressed in the blastemal compartment of the regenerating fin. esco2 is a critical regulator of fin regeneration and bone growth. esco2 and cx43 appear to function in a common pathway. A new model suggesting Cx43 acts downstream of, and may be regulated by, Esco2.